Treg-specific deletion of the phosphatase SHP-1 impairs control of inflammation in vivo - Gu, QinLei; Tung, Kenneth S.; Lorenz, Ulrike M. (Frontiers in Immunology, 2023)
To achieve a healthy and functional immune system, a delicate balance exists between the activation of conventional T cells (Tcon cells) and the suppression by regulatory T cells (Treg). The tyrosine phosphatase SHP-1, a negative regulator of TCR signaling, shapes this ‘activation-suppression’ balance by modulating Tcon cell resistance to Treg-mediated suppression. Treg cells also express SHP-1, but its role in influencing Treg function is still not fully understood. Here, we generated a Treg-specific SHP-1 deletion model, Foxp3Cre+ Shp-1f/f, to address how SHP-1 affects Treg function and thereby contributes to T cell homeostasis. We show that SHP-1 modulates Treg suppressive function at different levels. First, at the intracellular signaling level in Treg cells, SHP-1 attenuates TCR-dependent Akt phosphorylation, with loss of SHP-1 driving Treg cells towards a glycolysis pathway. At the functional level, SHP-1 expression limits the in vivo accumulation of CD44hiCD62Llo T cells within the steady state Tcon populations (both CD8+ as well as CD4+ Tcon). Further, SHP-1-deficient Treg cells are less efficient in suppressing inflammation in vivo; mechanistically, this appears to be due to a failure to survive or a defect in migration of SHP-1-deficient Treg cells to peripheral inflammation sites. Collectively, these data identify SHP-1 as an important intracellular mediator for fine-tuning the balance between Treg-mediated suppression and Tcon activation/resistance.